Distance Learning, E-Learning and Blended Learning in Mathematics Education International Trends in Research and Development (ICME-13 Monographs,, 2018)
This book builds on current and emerging research in distance learning, e-learning and blended learning. Specifically, it tests the boundaries of what is known by examining and discussing recent research and development in teaching and learning based on these modalities, with a focus on lifelong mathematics learning and teaching. The book is organized in four sections: The first section focuses on the incorporation of new technologies into mathematics classrooms through the construction or use of digital teaching and learning platforms. The second section presents a wide range of perspectives on the study and implementation of different tutoring systems and/or computer assisted math instruction. The third section presents four new innovations in mathematics learning and/or mathematics teacher education that involve the development of novel interfaces' for communicating mathematical ideas and analyzing student thinking and student work. Finally, the fourth section presents the latest work on the construction and implementation of new MOOCs and rich media platforms developed to carry out specialized mathematics teacher education.